How social stigma sustains the HIV treatment gap for MSM in Mpumalanga, South Africa. (December 2019) - Maleke, Kabelo; Daniels, Joseph; Lane, Tim; Struthers, Helen; McIntyre, James; Coates, Thomas
There are gaps in HIV care for men who have sex with men (MSM) in African settings, and HIV social stigma plays a significant role in sustaining these gaps. We conducted a three-year research project with 49 HIV-positive MSM in two districts in Mpumalanga Province, South Africa, to understand the factors that inform HIV care seeking behaviors. Semi-structured focus group discussions and interviews were conducted in IsiZulu, SiSwati, and some code-switching into English, and these were audio-recorded, transcribed, and translated into English. We used a constant comparison approach to analyze these data. HIV social stigma centered around gossip that sustained self-diagnosis and delayed clinical care with decisions to use traditional healers to mitigate the impact of gossip on their lives. More collaboration models are needed between traditional healers and health professionals to support the global goals for HIV testing and treatment.